Partial Differential Equations 1

Calculus Level 4

Solve 2 z x y = x 2 y \frac{{\partial}^{2} z}{\partial x \partial y} = {x}^{2} y given the conditions z ( x , 0 ) = x 2 z(x,0)={x}^{2} and z ( 1 , y ) = cos y z(1,y) = \cos {y} .

The solution is of the form z ( x , y ) = A x 3 y 2 + B cos y C y 2 + D x 2 1. z(x,y) = A{x}^{3} {y}^{2} + B \cos {y} - C{y}^{2} +D{x}^{2} -1. What is A + B + C + D A + B + C + D ?


The answer is 2.3333.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

I'm going to show a method to solve the PDE without knowing the form of the actual solution given (i.e. solving from scratch):

We have:

2 z x y = x 2 y \frac{\partial^2 z}{\partial x\partial y}=x^2y

z ( x , 0 ) = x 2 z(x,0)=x^2 , z ( 1 , y ) = cos ( y ) z(1,y)=\cos(y)

Integrate with respect to x x to obtain:

z y = 1 3 x 3 y + f ( y ) \frac{\partial z}{\partial y} = \frac{1}{3} x^3 y + f(y)

Where f ( y ) f(y) is some arbitrary function. Integrate again with respect to y y this time, obtaining:

z ( x , y ) = 1 6 x 3 y 2 + f ( y ) + g ( x ) z(x,y) = \frac{1}{6}x^3y^2 +f(y) +g(x)

Where g ( x ) g(x) is arbitrary and f ( y ) f(y) remains the same since the integral of an arbitrary function of y y with respect to y y is again an arbitrary function. Using boundary conditions, we have:

z ( x , 0 ) = x 2 = f ( 0 ) + g ( x ) z(x,0) = x^2 = f(0) +g(x)

z ( 1 , y ) = 1 6 y 2 + f ( y ) + g ( 1 ) = cos ( y ) z(1,y) = \frac{1}{6} y^2 +f(y) +g(1) =\cos(y)

We may now find f ( y ) f(y) and g ( x ) g(x) :

f ( y ) = cos ( y ) 1 6 y 2 g ( 1 ) f(y) = \cos(y) - \frac{1}{6}y^2 -g(1)

g ( x ) = x 2 + g ( 1 ) 1 g(x) = x^2 +g(1) -1

Returning to our original expression for z z we have:

z ( x , y ) = 1 6 x 3 y 2 + cos ( y ) 1 6 y 2 g ( 1 ) + x 2 + g ( 1 ) 1 z(x,y) = \frac{1}{6} x^3y^2 +\cos(y) -\frac{1}{6}y^2 -g(1) +x^2 +g(1) -1

From which it immediately follows that: A + B + C + D = 7 3 A+B+C+D = \frac{7}{3}

Chew-Seong Cheong
Dec 24, 2014

It is given that: z ( x , y ) = A x 3 y 2 + B cos y C y 2 + D x 2 1 \quad z(x,y) = Ax^3y^2+B\cos{y} - Cy^2+Dx^2-1

z ( x , 0 ) = 0 + B 0 + D x 2 1 = x 2 B = D = 1 \Rightarrow z(x,0) = 0 + B - 0 + Dx^2 - 1 = x^2\quad \Rightarrow B = D = 1

z ( 1 , y ) = A y 2 + cos y C y 2 + 1 1 = cos y A = C \Rightarrow z(1,y) = Ay^2+\cos{y} - Cy^2+1-1 = \cos{y} \quad \Rightarrow A = C

z ( x , y ) = A y 2 ( x 3 1 ) + cos y + x 2 1 \Rightarrow z(x,y) = Ay^2(x^3-1)+\cos{y} +x^2-1

Therefore,

z x = 3 A x 2 y 2 + 2 x \dfrac {\partial z} {\partial x} = 3Ax^2y^2 + 2x

2 z x y = 6 A x 2 y = x 2 y A = 1 6 \dfrac {\partial ^2 z} {\partial x \partial y} = 6Ax^2y = x^2y \quad \Rightarrow A = \frac {1}{6}

Therefore, A + B + C + D = 1 6 + 1 + 1 6 + 1 = 2 1 3 A+B+C+D = \frac {1}{6} + 1 + \frac {1}{6} + 1 = \boxed {2\frac{1}{3}}

I actually solved this from scratch, and never checked that we can just derive and match terms. I guess this problem is a good checking exercise.

Steven Zheng - 6 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...